C.29C>T polymorphism in the transforming growth factor-β1 (TGFB1) gene correlates with increased risk of urinary bladder cancer. Issue 2 (October 2015) - Gautam, Kirti Amresh; Pooja, Singh; Sankhwar, Satya Narayan; Sankhwar, Pushp Lata; Goel, Apul; Rajender, Singh
Highlights: c.29C>T in the TGFB1 gene correlates with increased risk of bladder cancer. c.29C>T increases the risk significantly in the recessive form. c.74G>C and +140A>G in the TGFB1 gene do not correlate with bladder cancer risk. Smokers with c.29C>T showed a stronger correlation with bladder cancer. Abstract: TGF-β1 is a pleiotropic cytokine, which plays a dual role in tumor development. In the early stages, it inhibits the growth of tumor while in the late stages of carcinoma, it promotes tumor growth. The purpose of this study was to analyze the distribution of the TGFB1 gene polymorphisms between cases and controls so as to assess their correlation with bladder cancer risk. This study included 237 cases of urinary bladder cancer and 290 age matched controls from the same ethnic background. Three polymorphisms in the TGFB1 gene, c.29C>T (rs-1800470), c.74G>C (rs-1800471) and +140A>G (rs-13447341), were analyzed by direct DNA sequencing. Statistical analyses revealed no significant differences in the demographical data, except that the frequencies of smokers and non-vegetarians were higher in the cases. Eighty percent of the bladder cancer patients had superficial transitional cell carcinoma, and 53.16% and 26.31% of the patients were in grade I and grade II, respectively. We found that c.29C>T substitution increased the risk of bladder cancer significantly and recessive model of analysis was the best fitted model ( p  = 0.004; OR = 1.72 95% CI 1.18–2.50). A significantly higher risk in the recessive form was also suggested by co-dominant analysis showing that the homozygous form (TT) was a significant risk factor in comparison to CC and CT genotypes. The other two polymorphisms, c.74G>C ( p  = 0.18, OR = 0.67 95% CI 0.37–1.21) and +140A>G ( p  = 0.416, OR = 0.77 95% CI 0.41–1.45) did not affect the risk of urinary bladder cancer. In conclusion, we found that the TGFB1 c.29C>T substitution increases the risk of bladder cancer significantly while c.74G>C and +140A>G polymorphisms do not affect the risk.